Covert job insecurity behind education, as a form of payment: the case of university internships (Praxis Educativa, 2017)
Internships are practice designed to give students a formative experience in specific workplaces. However, many social studies have pointed out how their low pay and legal costs favors the fraudulent use of interns as replacement jobs. In fact, interns have to perform similar tasks that workers do without equal pay and labor protections.In this article we propose to observe how these precarious conditions are concealed  behind the educational purpose of internships and their nonlabor legal consideration. This involves observing the social legitimacy of the image of education as a form of payment, which subsumes their labor problems. From a qualitative perspective, we propose to realize an analysis of the hegemonic speech on the internships, from the boarding of the voices of the legal system and of modals of the educational and labor world
Keywords: internships; precarious work; theory of human capital; education; work